PENINGKATAN KUAT TEKAN BETON POND ASH PENGGANTI SEBAGIAN AGREGAT HALUS BERDASARKAN FUNGSI WAKTU - Tumingan Tumingan; Salma Alwi; Rafian Tistro (Politeknik Negeri Jakarta, 2018)
ABSTRACTPond ash is a mixture of fly ash, bottom ash and other ash materials in a pond/lake/beach, pond ash materials are very overload and become waste, so the research of coal ash waste (pond ash) as a substitute of fine aggregate (sand) to increase the compressive strength of concrete influence of time function , were examined using cylindrical specimens of 100 mm diameter and 200 mm height. The specimens were made by taking a percentage ratio of pond ash by 0%: 5%: 10%: 15% and 20% in the mixture with a constant water cement ratio 0.49 based on the results of a normal concrete mix of f’c 25 MPa. The result of analysis of compressive strength to the time function obtained value at the age of 1 day the calculation results do not deviate from the equity line position, after the age of 3 and 7 days. The compressive strength test of concrete resulted in the value of over estimate means that the value of the test result is lower than the result of the equation can be stated that the hardening process of the concrete press is slow, while the age of 14, 28 days and so on the contrary is the result of compressive strength below the equity line or under estimate means the result value the test is higher than the result of the equation so that it can be stated that the process of hardening presses the concrete faster.Keywords: Coal Ash, Pond Ash, Compression strength concrete, time function.ABSTRAKPond ash adalah campuran bahan fly ash, bottom ash dan abu lainnya dalam sebuah kolam, bahan pond ash sangat melimpah dan menjadi limbah, maka di teliti pengaruh bahan limbah abu batubara (pond ash) sebagai pengganti sebagian agregat halus (pasir) terhadap peningkatan kuat tekan beton pengaruh fungsi waktu, diteliti menggunakan spesimen berbentuk silinder diameter 100 mm dan tinggi 200 mm. Spesimen dibuat dengan mengambil perbandingan prosentase pond ash sebesar 0%: 5%: 10%: 15% dan 20% terhadap campuran dengan faktor air semen konstan 0,49 berdasarkan rancangan campuran beton normal f’c 25 MPa. Hasil analisa pengujian kuat tekan terhadap fungsi waktu diperoleh nilai pada umur 1 hari hasil perhitungan tidak menyimpang dari posisi garis ekuitas, setelah umur 3 dan 7 hari, hasil perhitungan kuat tekan menghasilkan nilai over estimate berarti nilai hasil pengujian lebih rendah dari hasil persamaan dapat dinyatakan bahwa proses pengerasan kaut tekan beton lambat, sedangkan umur 14, 28 hari dan seterusnya terjadi sebaliknya yaitu menghasilkan kuat tekan dibawah garis ekuitas atau under estimate berarti nilai hasil pengujian lebih tinggi dari hasil persamaan sehingga dapat dinyatakan bahwa proses pengerasan kaut tekan beton semakin cepat.Kata Kunci : Abu Batubara, Pond ash, Kuat tekan Beton, fungsi waktu